1998
DOI: 10.1099/00222615-47-5-427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR-based methods and ribotyping performed with a mixture of PstI and SphI to differentiate strains of Salmonella serotype Enteritidis

Abstract: The capacity to differentiate Salmonella serotype Enteritidis strains by PCR ribotyping; RAPD typing with three arbitrary primers and ribotyping with a mixture of PstI and SphI or 'PS ribotyping', was evaluated on a series of 65 strains associated with human infections and 11 reference strains. The series had been analysed previously by phage typing and ribotyping performed with PstI and Sph I, separately. All methods typed all the strains; however, only ribotyping showed good reproducibility and sensitivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
(1 reference statement)
0
32
0
1
Order By: Relevance
“…At present, there is not a consensus as to which method is best suited for differentiation of serotype Enteritidis strains. Comparison of antibiotic resistance patterns (19), plasmid profiles (32,38), IS200 restriction fragment length polymorphism (31), ribotyping (16)(17)(18), and pulsed-field gel electrophoresis (PFGE) (20,27,34,35) have been used to differentiate strains for epidemi-ological purposes with various degrees of success. Also several PCR-based methods, such as random amplification of polymorphic DNA, have been used for this purpose, but these methods may lack sensitivity and reproducibility for routine use, and they do not appear to be suitably discriminatory due to the inability to separate artefactual variation and true polymorphism (18,36).…”
mentioning
confidence: 99%
“…At present, there is not a consensus as to which method is best suited for differentiation of serotype Enteritidis strains. Comparison of antibiotic resistance patterns (19), plasmid profiles (32,38), IS200 restriction fragment length polymorphism (31), ribotyping (16)(17)(18), and pulsed-field gel electrophoresis (PFGE) (20,27,34,35) have been used to differentiate strains for epidemi-ological purposes with various degrees of success. Also several PCR-based methods, such as random amplification of polymorphic DNA, have been used for this purpose, but these methods may lack sensitivity and reproducibility for routine use, and they do not appear to be suitably discriminatory due to the inability to separate artefactual variation and true polymorphism (18,36).…”
mentioning
confidence: 99%
“…While the stability of the ribotype patterns was not probed extensively here, repeat analysis of each isolate gave identical results in all but one instance. Similarly, Landeras and Mendoza (12) found that only a single band of about 7 kb, similar to the weak band that migrated at about 6.6 kb in this study, was not always reproducible and, hence, did not include that band in pattern analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of phage typing data, PFGE has not been effective for distinguishing S. enterica serotype Enteritidis PT 1 isolates from serotype Enteritidis PT 4 isolates due to pattern similarities (16). Randomly amplified polymorphic DNA (RAPD) analysis, PCR ribotyping, and typing by PCR for repetitive elements (M13 and the enterobacterial repetitive intergenic consensus sequence [ERIC]) have low indices of discrimination (9,11,12,15). This can create problems when clusters of similar isolates are detected within a short period of time and can result in extensive and costly epidemiologic investigations that are ultimately unproductive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nath et al [40] obtained a D value of 0.8978 for the serotype Typhi. In the case of the serotype Enteritidis, Landeras and Mendoza [44] reported a D value of 0.31, Soto et al [43] of 0.52, and Fernandez et al [45] of 0.68.…”
Section: Discussionmentioning
confidence: 99%